2012
DOI: 10.1109/tbme.2011.2180019
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram-Assisted Blood Pressure Estimation

Abstract: Accurate automatic noninvasive assessment of blood pressure (BP) presents a challenge due to conditions like arrhythmias, obesity, and postural changes that tend to obfuscate arterial amplitude pulsations sensed by the cuff. Researchers tried to overcome this challenge by analyzing oscillometric pulses with the aid of a higher fidelity signal-the electrocardiogram (ECG). Moreover, pulse transit time (PTT) was employed to provide an additional method for BP estimation. However, these methods were not fully deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(34 citation statements)
references
References 25 publications
1
32
0
1
Order By: Relevance
“…On the other side, in many works, the Pulse Transit Time (PTT), the time interval that heart beat transfers to a body peripheral, is used for the PWV estimation. Ahmad et al [5] and Xuan et al [6] showed that there is a significant correlation between BP and PTT, but this correlation depends on many parameters, which are varying among individuals [7], [4]. Many other works tried to fit regression models for BP estimation using PTT [8], [9], [10], but did not satisfy the standard criteria.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, in many works, the Pulse Transit Time (PTT), the time interval that heart beat transfers to a body peripheral, is used for the PWV estimation. Ahmad et al [5] and Xuan et al [6] showed that there is a significant correlation between BP and PTT, but this correlation depends on many parameters, which are varying among individuals [7], [4]. Many other works tried to fit regression models for BP estimation using PTT [8], [9], [10], but did not satisfy the standard criteria.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying principle of these devices is based on the relation of the time it takes for a volume of blood (in the form of a pulse) to travel from the heart to a peripheral organ, which could be in the form of pulse transit time (PTT) or pulse arrival time (PAT) [22][23][24]. Algorithms and mathematical models have been proposed and developed to optimize the regression process and calibration of the traveling/delay time ("Time Delay") and BP [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Lmt.) that has high accuracy [29]; and w is number of samples. Experiment results on datasets recorded from 10 subjects during relaxation and after exercise using equations (9) and (10) showed in Table V and Table VI. The results demonstrated the error of heart rate estimation in the RPD is more accurate compared to the ADT and LCM.…”
Section: Resultsmentioning
confidence: 99%